The complete mitochondrial genome sequences of five Otophysi species (Vertebrata, Teleostei) - Rodrigo Milan Calegari; Pedro Henrique Mira Rodrigues; Rodrigo Zeni dos Santos; Fausto Foresti; Ricardo Utsunomia; Fábio Porto-Foresti (Mitochondrial DNA. Part B. Resources, 2019)
Complete mitochondrial genomes of the characiform fishes Astyanax fasciatus, Astyanax altiparanae, Hoplias malabaricus (Karyomorph A) and the Gymnotiformes species Gymnotus sylvius and Gymnotus cuia were characterized in the present study. The whole mitogenomes varied from 16,400bp (A. fasciatus) to 17,730 bp (A. altiparanae) long and all of them consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNAs genes, a control region, and origin of light-strand replication. The gene order was similar among all the analyzed species. The nucleotide content of all mitogenomes was also similar, with 29.58–30.95% for A, 27.02–28.65% for T, 26.29–29.99% for C, and 14.41–15.67% for G.